Craniofacial growth and development: Tumbuh kembang kraniofasial - Marhamah; Sherly Horax; Fajriani; Irene Edith Rieuwpassa; Eddy Heriyanto Habar; Siti Rachmatiara (Makassar Dental Journal PDGI Makassar, 2024)
Growth is based on the concept of increasing the size and number of cells, development refers to the psychological condition and behavior of a person. The main stage of the process of growth and development in the formation of the human body is the formation of the craniofacial, which will then form the embryology of the oral cavity. The development and growth of the oral ca-vity occurs prenatally and postnatally starting from the fourth day which will continue into adulthood and experience negative growth during aging. Every human being goes through a period of prenatal growth. There are three periods in prenatal growth, namely preimplantation, embryonic and fetal. The three periods are sequential and continuous in forming the fetus. In general, humans have a pattern of growth and development which is the result of the interaction of many factors that affect growth and development. Anything can happen prenatally and postnatally, so attention and knowledge about embryology and develop-ment of the maxilla and mandible are needed.